Determination of contamination in the transept, la Esperanza - Casibare, of the lower reaches of the Buquepipe in the city of Villavicencio Meta Colombia - Castro-Garzón, Hernando, Rodríguez Miranda, Juan Pablo, Rivas Trujillo, Edwin, (International Journal of Advanced Science and Technology, 2020)
Through an exploratory-type quantitative procedure, applied to the urban properties adjacent to the lower channel of the Buquepipe in the municipality of Villavicencio Meta Colombia; a statistical correlation was carried out to determine the relationship between environmental problems present in the study transept and the sources of contamination. A conglomerate-type sampling was carried out establishing 100 farms for its intervention. Interviews were applied to collect information, which were structured according to the variables determined for the study; establishing that the solid waste pollution is the greatest impact on the area, showing a highly correlated with risk of flooding and landslides caused by the occupation of the round protection of the water body.